Soil Fertility and Quality Response to Reduced Tillage and Diversified Cropping under Organic Management. (1st March 2019) - Fernandez, Myriam R.; Zentner, Robert P.; Schellenberg, Michael P.; Aladenola, Olanike; Leeson, Julia Y.; Luce, Mervin St.; McConkey, Brian G.; Cutforth, Herb
Abstract : Core Ideas: A 6‐year organic field trial evaluated two tillage intensities (high and low) and two rotation sequences, simplified (wheat‐green manure) and diversified (wheat‐oilseed‐pulse‐green manure). Soil moisture and NO3‐N content were highest in the simplified rotation under high tillage. There were few soil P differences, although levels were higher for the low than high tillage in the simplified rotation. Reduced tillage intensity tended to increase soil organic C and decreased the percentage of erodible soil particles. Soil NO3‐N and PO4‐P content were also analyzed within the soil profile, down to 120 cm. During the past few decades, organic crop production in Canada and beyond has become increasingly widespread. In the Canadian Prairies, organic agriculture has traditionally relied on summer fallow and mechanical tillage for nutrient and pest management. More recently, there has been a substantial increase in the use of legume green manure, diversified crop rotations, and reduced tillage. Our objective was to determine if organic wheat ( Triticum aestivum L.) production using diversified crop rotations and reduced tillage could optimize production while minimizing its environmental impact within the Brown soil zone of Western Canada. A 6‐yr (2010 to 2015) field study evaluated two tillage intensities (high and low), and two rotation sequences, simplified (wheat–green manure) and diversified (wheat–oilseed–pulse–green manure). Precipitation throughout the study period was substantially greater than the long‐term mean. Spring soil NO3 −N and P content were highest in the first years of this trial. Soil moisture and NO3 −N content were highest in the simplified rotation under high tillage. There were few soil P differences, although levels were higher for the low than high tillage in the simplified rotation. Reduced tillage intensity tended to increase soil organic C and decreased the percentage of erodible soil particles. These soil quality changes would result in an increase in the soil's resistance to wind and water erosion, thus promoting environmental sustainability.